A randomized triple-blind controlled clinical trial evaluation of sitagliptin in the treatment of patients with non-alcoholic fatty liver diseases without diabetes - Doustmohammadian, Azam; Nezhadisalami, Ahmad; Safarnezhad Tameshke, Fahimeh; Motamed, Nima; Maadi, Mansooreh; Farahmand, Mohammad; Sohrabi, Masoudreza; Clark, Cain C. T.; Ajdarkosh, Hossein; Faraji, Amir Hossein; Nikkhah, Mehdi; Sobhrakhshankhah, Elham; et al. (Frontiers in Medicine, 2022)
The current study aimed to evaluate the efficacy of sitagliptin versus placebo in treating nonalcoholic fatty liver disease (NAFLD). In a triple-blind randomized clinical trial, we assigned 120 eligible subjects with NAFLD to receive daily dosing of 50 mg sitagliptin (n=60) or the placebo (n=60) for 56 weeks and lifestyle modification in both groups. Laboratory and anthropometric outcomes were measured, and liver stiffness was assessed using a fibroscan. The primary outcome measures were changes from baseline in fibrosis scores and liver transferases. Out of 120 patients randomized into sitagliptin and placebo groups, 76 patients completed the trial, of whom 44 were in the sitagliptin and 32 in the placebo groups. Patients receiving sitagliptin showed a significant decrease in the fibrosis scores (P=0.001). The reductions in the alanine aminotransferase (P=0.036) and aspartate aminotransferase (P<0.001) levels were also statistically significant. The effect of sitagliptin in reducing fibrosis scores was significantly greater in normal-weight and overweight individuals than in obese individuals (p=0.036, and p=0.018, respectively), whereas the effects of sitagliptin on AST levels were greater among overweight/obese patients (p=0.028, and p=0.016, respectively). Sitagliptin reduced fibrosis scores and liver enzymes in NAFLD patients after 56 weeks of therapy. The changes in fibrosis scores were more prominent in patients with normal weight and overweight than obese patients, whereas the effects on AST levels were greater among overweight/obese patients. Other randomized trials with larger sample sizes and longer treatment durations may be required before precise results can be reached.